HOTS QUESTIONING ABILITY AND HOTS PERCEPTION OF LANGUAGE TEACHERS IN INDONESIA - Gozali, Imelda; Lie, Anita; Tamah, Siti Mina; Jemadi, Fransiskus (Universitas Pendidikan Indonesia, 2021)
This study is part of a larger-scale research aimed at mapping the pedagogical competence of teachers of English and Indonesian Language across three cities of differing demographic features in Indonesia. As a subset of the study, this paper focused on investigating the ability to formulate higher-order thinking (HOT) questions in the classroom among the teachers, as well as getting their perception about applying HOTS in their classes. The mapping was done by comparing the abilities across teachers’ regions, years of service, and subjects taught (English and Indonesian Language). This research was designed as a case study involving quantitative and qualitative data analyses, with 15 (fifteen) secondary school teachers as the participants. Data were collected through classroom observations, document (lesson plan) analyses, as well as teachers’ interviews. Quantitative analysis was performed on the teachers’ scores in formulating HOTS questions, while teaching documents and transcripts were coded for qualitative analysis. Although the statistical results revealed no significant difference between the HOTS questioning scores of the teachers in the different regions and years of service, qualitative data suggested that language medium, as shown by the difference between English and Indonesian Language teachers, might be an important factor affecting the abilities of teachers to ask HOT questions, as well as their perception of the applicability of HOTS in their classes. The inquiry into the teachers’ perceptions of HOTS also displayed a gap between teachers in the bigger city and those in more remote regions, as well as between the novices and the practitioners.